Efeitos do uso do solo na estrutura e composição de invertebrados aquáticos e no processo de decomposição foliar em riachos neotropicais - Malacarne, Tássia Juliane (2015)
Different land uses directly affect the characteristics of a river basin, reflecting the health and integrity of the aquatic environment, and consequently influence the aquatic biota and ecosystem processes. This study aimed to analyze the structure and community composition of aquatic invertebrates and the role of these organisms in the process of decomposition of leaf litter in streams with different land uses. Samples were collected in the period from September to December 2013 in five streams of western Paraná. At each stream were placed 18 bags containing litter for colonization by aquatic invertebrates during the exposure times of 15, 30, 45, 60, 75 and 90 days. Significant spatial differences in the structure and composition of the community of aquatic invertebrates in the studied streams were recorded. There were no significant differences in the activity of aquatic invertebrates in the leaf decomposition process streams with different land uses. But there were differences in the variability of decomposition between the streams, and the reference stream showed lower variability in the decomposition process. This result may have been influenced by habitat quality, availability of organic matter, and the structure and composition of benthic community present in the reference stream, which differs significantly between locations with different types of land use. The results of this study demonstrate that human interference in the aquatic environment through land use can influence negativity in ecosystem processes, particularly in invertebrate activity during the processing of allochthonous material, as well as modify the structure and composition of the biota.